Analisis Pengaruh Nilai yang Dirasakan dan Kepuasan Terhadap Loyalitas Pasien Puskesmas di Kota Samarinda - Noor Hariyani; Ratno Andrianto; Nur Rohmah; Rahmat Bakhtiar; Irfansyah Baharuddin Pakki; Ida Ayu Indira Dwika Lestari; Dian Ayu Fitriani (Universitas Pahlawan Tuanku Tambusai, 2026)
Service quality in public health centers (Puskesmas) plays a crucial role in shaping patient perceptions and behaviors, which in turn influence patient loyalty. In Samarinda City, declines in patient visits and the achievement of Minimum Service Standards (MSS) indicate ongoing challenges in primary healthcare services. This study aims to analyze the effects of perceived value and patient satisfaction on patient loyalty at Puskesmas. Using a quantitative approach with a cross-sectional design, the study involved 420 respondents selected through cluster random sampling and convenience sampling. Data were collected using questionnaires that had been tested for validity and reliability and were analyzed using path analysis. The results show that perceived value has a positive and significant effect on patient loyalty (β = 0.2405), while patient satisfaction demonstrates a stronger influence on loyalty (β = 0.3410). In addition, patient satisfaction mediates the relationship between perceived value and loyalty, whereas perceived value acts as a mediating variable in the relationship between satisfaction and loyalty. These findings confirm that patient loyalty is shaped not only by direct effects but also through reciprocal mediating relationships between perceived value and patient satisfaction.